ANALISIS RISIKO MUSCULOSKELETAL DISORDERS MENGGUNAGAKN METODE RULA TERHADAP POSTUR KERJA PADA AKTIVITAS PROYEK - Rian Roni Abdurrohim (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2021)
One of the important assets for the sustainability of a company is human resources or workers. However, companies often ignore the needs and comfort of workers. Not a few companies that do not apply methods in accordance with standard procedures, as well as work facilities that do not support the process of their workers' activities. Ergonomic aspects must be considered in the work process so that it will not cause complaints on the workers' body parts. Complaints of Musculoskeletal Disorders (MSD) are one of the threats caused by discomfort in body position while working. The risk of developing Musculoskeletal Disorders (MSD) complaints is analyzed in this study by observing the worker's body posture in routine activities carried out in development projects. The analysis was carried out using the RULA method which provides an assessment of each position of the worker's upper body. Based on the results of data processing using the RULA method, a score level for the posture of workers in plastering activities is worth 5. The score indicates a moderate level of risk, therefore further investigation is needed to make changes as soon as possible.